2019
DOI: 10.1183/23120541.00075-2019
|View full text |Cite|
|
Sign up to set email alerts
|

Sex-specific differences and survival in patients with idiopathic pulmonary arterial hypertension 2008–2016

Abstract: BackgroundWomen with idiopathic pulmonary arterial hypertension (IPAH) have been found to have a worse haemodynamic status at diagnosis, but better survival than men. Over the past decade, demographics have changed and new treatments have become available. The objective of this study was to investigate sex differences in an incident IPAH population diagnosed between 2008 and 2016.MethodsDifferences in clinical characteristics of patients included in the Swedish Pulmonary Arterial Hypertension Register (SPAHR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 29 publications
2
9
0
1
Order By: Relevance
“…The study population showed a near-equal distribution between women and men. Interestingly, our cohort is quite comparable to that of the Swedish Pulmonary Arterial Hypertension Registry, which has been published recently (17). Absence of female predominance in the present study may be related to sample size and yet-unclear evolution of referral biases (17).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The study population showed a near-equal distribution between women and men. Interestingly, our cohort is quite comparable to that of the Swedish Pulmonary Arterial Hypertension Registry, which has been published recently (17). Absence of female predominance in the present study may be related to sample size and yet-unclear evolution of referral biases (17).…”
Section: Discussionsupporting
confidence: 75%
“…Interestingly, our cohort is quite comparable to that of the Swedish Pulmonary Arterial Hypertension Registry, which has been published recently (17). Absence of female predominance in the present study may be related to sample size and yet-unclear evolution of referral biases (17). Diastolic echocardiographic indexes of ventricular function were not assessed and need further evaluation since echocardiography is more accessible than CMR in most PH centers.…”
Section: Discussionsupporting
confidence: 62%
“…A greater proportion of female PAH patients has been noted in several registries, ranging from 56% to 86%, implicating female sex as a risk factor for PAH [18,[20][21][22][23][24][25][26]. As seen in the COMPERA registry, this higher female to male ratio 2.3:1 in younger patients (median 54 years) seems to decrease as age at diagnosis rises (1.2:1 in 75-year-old patients) along with the onset of menopause [18].…”
Section: Epidemiologymentioning
confidence: 99%
“…Due to the female predominance in many forms of pulmonary arterial hypertension [17], additional comparisons were implemented between female and male patients, as well as pre-vs. post-iEPO effects for female patients.…”
Section: Data Collectionmentioning
confidence: 99%